Differential effect of cigarette smoke exposure on exhaled nitric oxide and blood eosinophils in healthy and asthmatic individuals - Jacinto, Tiago (2019)
Background: Tobacco smoking affects both the fraction of exhaled nitric oxide (FeNO) and blood eosinophil (B-Eos) count, two clinically useful biomarkers in respiratory disease that represent local and systemic type-2 inflammation, respectively. Objective: We aimed to study the influence of objectively measured smoke exposure on FeNO and B-Eos in a large population of subjects with and without asthma. Methods: We utilized the US National Health and Nutrition Examination Surveys 2007–2012 and included 10 669 subjects aged 6–80 years: 9869 controls and 800 asthmatics. Controls were defined as having no respiratory disease, no hay fever in the past year, and B-Eos count ≤0.3 × 109 l−1. Asthma was defined as self-reported current asthma and at least one episode of wheezing or an asthma attack in the past year, but no emphysema or chronic bronchitis. Tobacco use was collected via questionnaires and serum cotinine was measured with mass spectrometry. Results: Increasing cotinine levels were associated with a progressive reduction in FeNO in both controls and asthmatics. FeNO remained significantly higher in asthmatics than controls except in the highest cotinine decile, equivalent to an average reported consumption of 13 cigarettes/day. B-Eos count increased with cotinine in controls, but was unchanging in asthmatics. Interestingly, B-Eos count was significantly higher in presently non-exposed (cotinine below detection limit) former smokers than never smokers. Conclusion: Smoke exposure decreases FeNO and increases B-Eos count. These effects should be considered in the development of normalized values and their interpretation in clinical practice. The persistence of elevated B-Eos in former smokers warrants further studies.